Polyculture of small fish species (Systomus sarana, Pethia ticto and Rasbora daniconius) with Indian - Debbarma, Supriya; Minare, Anubhuti; Vyas, Vipin (AG Volumes, 2025)
The present study aimed to evaluate the growth performance and survival of small indigenous fish species Systomus sarana, Pethia ticto, and Rasbora daniconius in polyculture with Indian Major Carps (IMCs) including Labeo rohita, Catla catla, and Cirrhinus mrigala. The experiment was conducted from August to December in the Shade-II hatchery of the Department of Zoology and Applied Aquaculture, Barkatullah University, Bhopal. Two treatments were designed: Treatment-1 (T1) consisted of both IMCs and small fish species, while Treatment-2 (T2) included only the small fish species. Each tank held 60 individuals, and both were managed under similar feeding, fertilization, and water quality monitoring protocols. Water quality parameters such as temperature, pH, dissolved oxygen, free CO₂, total alkalinity, and hardness remained within optimal ranges for fish growth throughout the culture period. The final average weights of small fish species were slightly higher in T2 (e.g., Rasbora daniconius 9.41 g) compared to T1 (9.29 g), suggesting mild competition for resources in the mixed stocking environment. Among IMCs, Cirrhinus mrigala exhibited the highest growth (13.47 g). Survival rates were high in both treatments, with T2 showing a slightly better average (86.6%) than T1 (82.35%). The results indicate that small indigenous fish species can be co-cultured with IMCs without significantly compromising their growth or survival, offering a promising approach for enhancing fish yield and biodiversity in freshwater aquaculture systems.